Hubungan Peran Orang Tuadan Teman Sebaya dengan Perilaku Pencegahan Penyakit Menular Seksual (PMS) pada Remaja di SMK - Ihtiara Ria Dini; Meida Laely Ramadani (Journal of Bionursing, 2020)
Background:Teenagers experience physical, cognitive, socio emotional development. Curiosity and sexual fantasy cause teens to want to practice what adults do. Peers and the role of parents also play a very strong role in the attitude and prevention of sexually transmitted diseases (STDs). The role of parents is also important in the personal formation of adolescents. Parents have the role of helping teen  increase self-confidence and teach teenagers to make decisions so as not to be influenced by their friends.Objective : To find out the relationship between the role of parents and peers with the prevention of sexually transmitted diseases (STDs) in adolescents at SMK Maarif Nu 1 Ajibarang.Method: This research is a quantitative descriptive study using cross sectional method. The sample of this study is the eleventh grade students namely 94 respondents taken by proportional random sampling. Questionnaire sheet is used to measure the instruments.Result: A total of 55 respondents (58.5%) and there are 73.4% respondents who are 17 years old. 64.9% Respondents received good influence from peers and 84.0% respondents with the good parents role. There are 53.2% adolescents with bad sexually transmitted disease prevention behaviors. The results of the analysis of peer variables and sexually transmitted disease prevention behaviors showed a significant relationship, with a p value = 0.002, and the role of parents with the prevention of sexually transmitted diseases also showed a significant relationship, with a p value = 0.005.Conclusion: There is a relationship between the role of parents and peers with the prevention of sexually transmitted diseases in SMK.